From calibration to identifiability analysis: Using a multi-reserve DEB model to understand holopelagic Sargassum spp. growth - María-José Lagunes; Gonçalo M. Marques; Evelyn R. Salas-Acosta; Roman M. Vásquez-Elizondo; Thierry Thibaut; Daniel Robledo; Solène Connan; Valérie Stiger-Pouvreau; Léo Berline; Christophe Lett; Laure Pecquerie (Ecological Modelling, 2026)

Rare Sex and a Long Life Sustain Seaweed Populations at the Warm Edge of Their Range - Sofie Vranken; Frédérique Steen; Sofie D'hondt; Marc Verlaque; Conxi Rodríguez‐Prieto; Christophe Vieira; Thierry Thibaut; Kenny Bogaert; Olivier De Clerck (Journal of Biogeography, 2026)
Aim The life cycle of many organisms is all but fixed across their distribution range. Most commonly, populations respond to environmental variation by shifting the timing of reproductive events (phenology). More profoundly, populations may (partly) shift their mode of reproduction from sexual to asexual. Life cycle variation can impact reproductive success, gene flow, genetic diversity and, ultimately, the evolutionary trajectory of populations. Understanding the factors that influence life cycle variation is essential for grasping the biology and ecological roles of species. This study investigates the variation in life cycles and its effects on the genetic diversity of a brown seaweed, Dictyota , across its European range. Location North‐East Atlantic Ocean and the Mediterranean Sea. Taxon Dictyota dichotoma (Hudson) J.V. Lamouroux (Phaeophyceae, Dictyotales). Methods We monitored phenology, fertility and lifespan in Atlantic and Mediterranean populations at its northern and southern boundaries and used microsatellite markers to assess how these factors influence genetic and genotypic diversity. Results We observed significant differences in phenology, reproductive strategies and genetic diversity among northern and southern European populations. In Mediterranean populations, D. dichotoma exhibited sporophytic dominance with gametophytes being extremely rare, suggesting a shift towards asexual reproduction. In contrast, North‐East Atlantic populations displayed more pronounced seasonal reproductive patterns with higher frequencies of gametophytes, indicating predominant sexual reproduction. However, genetic analysis showed lower allelic richness and unique alleles in northern populations, whereas southern populations were genetically more diverse, reflecting historical biogeographic processes. Clonal reproduction was more pronounced in the Mediterranean populations, influencing the spatial genetic substructure and contributing to locally lower genotypic diversity compared to Atlantic populations. Main Conclusions Our findings demonstrate that life cycle variation and phenology in D. dichotoma are closely tied to regional environmental conditions and have significant implications for population structure and genetic diversity. Results highlight how shifts in reproductive strategies contribute to the evolutionary and ecological dynamics of marine macroalgae across biogeographical gradients.

Metrological concepts applied to Total Alkalinity measurements in seawater: reference materials, inter-laboratory comparison and uncertainty budget - Gaëlle Capitaine; Samir Alliouane; Thierry Cariou; Jonathan Fin; Paola Fisicaro; Thibaut Wagener (Ocean Science, 2026)
Total alkalinity (TA) measurements in seawater are crucial for characterizing and monitoring the oceanic carbonate system. While international best practices and guidelines exist, the field still lacks widely available traceable reference materials and a well-established uncertainty budget of the measurement method. In this study, we applied key metrological principles – development of reference materials, inter-laboratory comparison and uncertainty quantification – to TA measurements. We developed two reference materials, including an artificial material with a rigorously characterized reference value and an associated uncertainty budget, being traceable to the International System of units (SI). These materials were tested in an inter-laboratory comparison involving five laboratories and demonstrated the applicability of the reference materials developed for quality control. Additionally, we established an uncertainty budget for the TA measurement method using two metrological approaches. The resulting expanded uncertainty was 5 µmol kg−1 (with a coverage factor k=2) in TA, approaching the 4 µmol kg−1 target set by the Global Ocean Acidification Observing Network for climate monitoring. These findings mark a significant step toward improving the quality and comparability of TA measurements, thereby strengthening long-term ocean carbonate system monitoring.

An ecosystem-based index for Mediterranean coralligenous reefs: A protocol to assess the quality of a complex key habitat - Patrick Astruch; Charles-François Boudouresque; Mélanie Cabral; Thomas Schohn; Enric Ballesteros; Denise Bellan-Santini; Bruno Belloni; Carlo Nike Bianchi; Olivia Cassetti; Pierre Chevaldonné; Maïa Fourt; Paolo Guidetti; et al. (Marine Pollution Bulletin, 2025)

Distribution, population structure and life cycle of the Mediterranean endemic Laminaria rodriguezii (Laminariales, Phaeophyceae) - THIBAUT THIERRY; AURÉLIE BLANFUNÉ; BASTIEN THOUROUDE; LAURIC REYNES; LAURENT BALLESTA; FLORIAN HOLON; JULIE DETER; CHARLES-FRANÇOIS BOUDOURESQUE; KLAUS-ULRICH VALENTIN; ANDREAS WAGNER; INKA BARTSCH (Mediterranean Marine Science, 2025)
Laminaria rodriguezii is a rare deep-water kelp species, endemic to the Mediterranean Sea, known in only 19 locations, 5 along the Eastern Provence and 14 in Corsica (French coasts). Populations are found at depths ranging from 48 to 100 m; the oldest record dates back to 1954. This study aims to better understand its distribution, biology, and ecology by analyzing recent data from in situ observations and sampling. In July 2019, a population at Magaud Bank (France) was studied at 75 m depth. A total of 154 individuals were collected in quadrats, showing an average density of 15.7 ± 2.2 individuals per m2 (mean ± SE). The population consists mostly of small blades, with 80% measuring

Correction: Ecosystem-based assessment of a widespread Mediterranean marine habitat: The Coastal Detrital Bottoms, with a special focus on epibenthic assemblages - Patrick Astruch; Ameline Orts; Thomas Schohn; Bruno Belloni; Enric Ballesteros; Daniela Bănaru; Carlo Nike Bianchi; Charles-François Boudouresque; Thomas Changeux; Pierre Chevaldonné; Jean-Georges Harmelin; Noëmie Michez; et al. (Frontiers in Marine Science, 2025)

Chaotic and long-term trends in Berre Lagoon (Provence, France): a shift towards alien-dominated assemblages? - PATRICK ASTRUCH; THOMAS SCHOHN; FRÉDÉRIC ANDRÉ; BRUNO BELLONI; CHARLES-FRANÇOIS BOUDOURESQUE; CHRISTOPHE LEJEUSNE; NICOLAS MAYOT; GUILLAUME MARCHESSAUX; THIERRY THIBAUT; HELMUT ZIBROWIUS; MARC VERLAQUE (Mediterranean Marine Science, 2025)
Over historical time, Berre Lagoon (SE France, NW Mediterranean Sea) had undergone various changes. These became more significant, transforming and even disruptive since the 19th century when the channel connecting the lagoon to the sea was deepened and the surrounding areas were industrialized and urbanized. Pollution and anoxic crises were major consequences. Concomitantly, many non-indigenous species (NIS) arrived in the lagoon. In recent years, climate change and freshwater input from a hydro-electric power plant have been the main drivers influencing the lagoon ecosystem. The major anoxic crisis of 2018 caused the lagoon ecosystem to collapse. In the following years, an increase in mean salinity linked with low precipitation in the regional watershed and the resulting lower freshwater input from the hydro-electric power plant caused rapid changes in ecological assemblages and favoured newly arrived NIS. An updated list of NIS and cryptogenic species (38 taxa according to the last census) is presented here. The species introduction rate has strongly increased since 2000, or at least the recognition rate. Temporal and spatial changes are discussed for major NIS in Berre Lagoon. The success of new NIS is interpreted as a consequence of the 2018 crisis, of global change and of re-marinization of the water body related to dryer periods and stricter freshwater input regulation.

Non-Indigenous Species of Macroalgae in French Mediterranean Marine Protected Areas: Distribution and Trends - Marie Borriglione; Sandrine Ruitton; Aurélie Blanfuné; Michèle Perret-Boudouresque; Bastien Thouroude; Marc Verlaque; Charles-François Boudouresque; Thierry Thibaut (Journal of Marine Science and Engineering, 2025)
The Mediterranean Sea, a biodiversity hotspot, faces significant threats from non-indigenous species (NIS), which drive biodiversity changes. Over the past century, the introduction of NIS has accelerated due to maritime traffic, aquaculture, and interoceanic canals, fostering biological invasions. Marine protected areas (MPAs), established to preserve biodiversity, are increasingly impacted. This review quantified and characterized French Mediterranean MPAs, analyzing non-indigenous macroalgae distribution based on the existing literature and the authors’ observations. Results revealed widespread occurrence, with the highest NIS richness in strictly regulated MPAs; their proximity to large harbors highlights the paramount importance of the introduction pathways. In addition, there is a significant knowledge gap regarding the distribution of NIS within MPAs, complicating efforts to monitor and study these species effectively. These findings highlight the challenges in monitoring and managing invasions and the urgent need for controlling primary and secondary invasion pathways, within and outside the MPAs, international collaboration to control them, and enhanced funding for NIS monitoring. Without adaptive management, even strictly protected MPAs are vulnerable to the escalating impacts of invasive species.

Understanding the ecosystem quality of Mediterranean shallow rocky reefs: Insights from the application of ecosystem-based indices - Élodie Jacob; Mélanie Cabral; Thomas Schohn; Bruno Belloni; Charles-François Boudouresque; Thierry Thibaut; Sandrine Ruitton; Patrick Astruch (Marine Pollution Bulletin, 2024)

Impact of the invasive brown alga Rugulopteryx okamurae on the benthic communities in the Northwestern Mediterranean Sea - Marie Borriglione; Sandrine Ruitton; Florian Boyer; Delphine Thibault; Aurélie Blanfuné; Dorian Guillemain; Marc Verlaque; Charles-François Boudouresque; Thierry Thibaut (Estuarine, Coastal and Shelf Science, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Distribution, health and threats to Mediterranean macroalgal forests: defining the baselines for their conservation and restoration - Jana Verdura; Lluc Rehues; Luisa Mangialajo; Simonetta Fraschetti; Zahira Belattmania; Silvia Bianchelli; Aurélie Blanfuné; Brahim Sabour; Antonia Chiarore; Roberto Danovaro; Erika Fabbrizzi; Sylvaine Giakoumi; et al. (Frontiers in Marine Science, 2023)
The worldwide decline of macroalgal forests is raising major concerns for the potentially negative consequences on biodiversity and ecosystem functions, pushing for the definition of specific conservation and restoration measures. Protecting and restoring these habitats requires detailed information on their distribution, ecological status, and drivers of decline. Here, we provide the most updated available information on the distribution of Mediterranean Cystoseira s.l. forests by conducting a comprehensive bibliographic survey of literature published from 2009 to 2021, complemented by unpublished data. We also provide insights into the ecological status of these forests and the stressors affecting them across the Mediterranean basin. Our results show that most Mediterranean coasts remain un(der)studied and that the available information is concentrated in spatially limited coastal areas, restricted to very few species. When the ecological status is reported, data is highly heterogeneous, making any comparisons problematic, what claims for the description and use of easy and standardized monitoring methods for comparative purposes. Drivers of decline of Cystoseira s.l. forest have been even less investigated and, therefore, still poorly characterized. Our results highlight that our current knowledge is still insufficient to implement effective conservation and restoration strategies at the basin scale but also regionally. We call for the urgent need for mapping and standardized monitoring of Cystoseira s.l. forests to obtain baseline information for future management strategies involving their conservation, the mitigation of the stressors threatening them and the restoration of the degraded forests.

Ecosystem-based assessment of a widespread Mediterranean marine habitat: The Coastal Detrital Bottoms, with a special focus on epibenthic assemblages - Patrick Astruch; Ameline Orts; Thomas Schohn; Bruno Belloni; Enric Ballesteros; Daniela Bănaru; Carlo Nike Bianchi; Charles-François Boudouresque; Thomas Changeux; Pierre Chevaldonné; Jean-Georges Harmelin; Noëmie Michez; et al. (Frontiers in Marine Science, 2023)
Introduction Coastal detrital bottoms (CDB) are one of the most extensive habitats of the continental shelf worldwide, in the upper levels of the circalittoral zone. Hosting a diverse community structured by sediment grain size, trophic interactions and calcified organisms, CDB exhibit important ecological functions. In the Mediterranean Sea, CDB are constituted by recent elements partly provided by adjacent infralittoral and circalittoral ecosystems. Since the 2010s, the offshore extension of many Marine Protected Areas (MPAs) has resulted in the incorporation of vast areas of CDB, raising the issue of their management. The Marine Strategy Framework Directive (MSFD) has embraced the concept of an ecosystem-based approach involving taking into account the functioning of marine habitats and their related ecosystem services. The purpose of this paper is to propose an ecosystem-based quality index (EBQI) tested on CDB from the north-western Mediterranean Sea, focusing mainly on epibenthic assemblages. Methods The first step has been to define a conceptual model of the CDB functioning, including the main trophic compartments and their relative weighting, then to identify appropriate assessment methods and potential descriptors. Twenty-nine sites were sampled along the coast of Provence and French Riviera (Southern France). Study sites were chosen with a view to encompassing a wide range of hydrological conditions and human pressures. Results Very well-preserved sites were found in Provence in areas without trawling and terrigenous inputs, while impacted and low-ES sites were located in the vicinity of urbanized areas. The cover of rhodoliths characterizes the seascape and might be an indicator of the good ES of CDB and reduced human pressure. However, the absence of rhodoliths may also be induced by natural phenomena. Discussion The EBQI designed for CDB proved representative and useful for a functional assessment based on epibenthic assemblages. However, some descriptors have shown their limitations and should be further explored. We highlight here the priority of establishing an index corresponding to a societal demand (e.g., European Directives, Barcelona convention) as a basis for a broad and large-scale assessment, for practical reasons. We stress the need to better apprehend the role of the macro-infauna and to extend this index over a wider geographical scale.

Consistent genetic divergence observed among pelagic Sargassum morphotypes in the western North Atlantic - Skye Dibner; Lindsay Martin; Thierry Thibaut; Didier Aurelle; Aurélie Blanfuné; Kerry Whittaker; Laura Cooney; Jeffrey M. Schell; Deborah S. Goodwin; Amy N. S. Siuda (Marine Ecology, 2022)
Sargassum natans and Sargassum fluitans are uniquely holopelagic macroalgae, providing open ocean nursery and foraging habitat for commercially and ecologically important species. Recent basin‐wide changes in pelagic Sargassum diversity and distribution have manifested in proliferation of a previously rare morphotype, Sargassum natans VIII , to rival biomass levels of historically dominant S . natans I and S . fluitans III . Precise genetic identification of these morphotypes can improve accuracy and interpretation of ecological studies as well as clarify evolutionary history and population connectivity. For 139 field samples collected from the subtropical and tropical North Atlantic, three mitochondrial genes (cox3, nad6, and mt16S rRNA) were used to examine genetic divergence among the three common pelagic Sargassum morphotypes. These gene sequences successfully differentiated among morphotypes regardless of geographic origin, confirming in situ morphology‐based identifications. Sargassum natans I and S . natans VIII exhibited divergence consistent with that between the S . natans ‐complex and S . fluitans III . Phylogenetic analysis of these samples also indicated evolutionary divergence between Sargassum morphologies. The genetic divergence among morphotypes, compared with benthic Sargassum species, suggested that taxonomic reclassification of the three most common pelagic morphotypes may be warranted.

The Three-Dimensional Structure of Mediterranean Shallow Rocky Reefs: Use of Photogrammetry-Based Descriptors to Assess Its Influence on Associated Teleost Assemblages - Tiffany Monfort; Adrien Cheminée; Olivier Bianchimani; Pierre Drap; Arthur Puzenat; Thierry Thibaut (Frontiers in Marine Science, 2021)
In the Mediterranean Sea, shallow rocky reefs and the associated three-dimensional (3D) structure support rich and abundant communities; they are therefore of functional importance, in particular for the renewal of fish stocks. However, these habitats and their functions are likely to be altered by anthropogenic pressures inducing habitat transformations. It is therefore necessary to assess their 3D structure, their transformations and relationship to communities, especially for management and conservation purposes. In this article we aimed (i) to compare two methods that quantify the metrics of the 3D structure (rugosity) of shallow rocky reefs (chain-and-tape method and photogrammetry), and (ii) to quantify the possible links between this habitat structure and the fish assemblages. We found that photogrammetry and the chain-and-tape method yielded a similar estimate of rugosity, but photogrammetry was the most efficient method in terms of measurement quality and time (when considering in-water acquisition). This method also displayed the best repeatability. The 3D habitat descriptors (mean surface rugosity, variation of surface rugosity, and depth) differed significantly between the studied sites and were therefore included as covariables. Total fish abundance and species richness increased with higher mean surface rugosity. In addition, the composition of fish assemblages was significantly influenced by surface rugosity, although this effect was modulated by depth. When focusing on specific taxa, neither density patterns nor size class distributions displayed clear patterns in relation to rugosity metrics. However, this study demonstrated that spatial variability of teleost fish assemblages can be explained by habitat rugosity which probably increases the number of shelters and food resources, and therefore improves chances of survival. In addition, our study has shown that photogrammetry is an appropriate method to assess 3D structure metrics in a temperate rocky reef.

Population Genomics and Lagrangian Modeling Shed Light on Dispersal Events in the Mediterranean Endemic Ericaria zosteroides (=Cystoseira zosteroides) (Fucales) - Lauric Reynes; Didier Aurelle; Cristele Chevalier; Christel Pinazo; Myriam Valero; Stéphane Mauger; Stéphane Sartoretto; Aurélie Blanfuné; Sandrine Ruitton; Charles-François Boudouresque; Marc Verlaque; Thierry Thibaut (Frontiers in Marine Science, 2021)
Dispersal is a central process that affects population growth, gene flow, and ultimately species persistence. Here we investigate the extent to which gene flow occurs between fragmented populations of the deep-water brown algae Ericaria zosteroides (Turner) Greville (Sargassaceae, Fucales). These investigations were performed at different spatial scales from the bay of Marseille (western Provence) to Corsica. As dispersal of zygotes is shown to be limited over distances beyond a few meters, we used a multidisciplinary approach, based on Lagrangian modeling and population genomics to test the hypothesis that drifting of fertile parts of thallus (eggs on fertile branches), mediated by ocean currents, enable occasional gene flow between populations. Therefore we assessed the respective contribution of oceanographic connectivity, geographical isolation, and seawater temperatures to the genetic structure of this species. The genetic structure was assessed using 10,755 neutral SNPs and 12 outlier SNPs genotyped by dd-RAD sequencing in 261 individuals of E. zosteroides . We find that oceanographic connectivity is the best predictor of genetic structure, while differentiation in outlier SNPs can be explained by the depth of populations, as emphasized by the minimum seawater temperature predictor. However, further investigations will be necessary for clarifying how depth drives adaptive genetic differentiation in E. zosteroides . Our analyses revealed that local hydrodynamic conditions are correlated with the very high divergence of one population in the Bay of Marseille. Overall, the levels of gene flow mediated by drifting were certainly not sufficient to counteract differentiation by local genetic drift, but enough to allow colonization several kilometers away. This study stresses the need to consider secondary dispersal mechanisms of presumed low dispersal marine species to improve inference of population connectivity.

Seasonal and Interannual Variability of the CO2 System in the Eastern Mediterranean Sea: A Case Study in the North Western Levantine Basin - Cathy Wimart-Rousseau; Thibaut Wagener; Marta Álvarez; Thierry Moutin; Marine Fourrier; Laurent Coppola; Laure Niclas-Chirurgien; Patrick Raimbault; Fabrizio D’Ortenzio; Xavier Durrieu de Madron; Vincent Taillandier; Franck Dumas; et al. (Frontiers in Marine Science, 2021)
The seasonal variability of the carbonate system in the eastern Mediterranean Sea (EMed) was investigated based on discrete total alkalinity (A T ), total dissolved inorganic carbon (C T ), and pH measurements collected during three cruises around Crete between June 2018 and March 2019. This study presents a detailed description of this new carbonate chemistry dataset in the eastern Mediterranean Sea. We show that the North Western Levantine Basin (NWLB) is unique in terms of range of A T variation vs. C T variation in the upper water column over an annual cycle. The reasons for this singularity of the NWLB can be explained by the interplay between strong evaporation and the concomitant consumption of C T by autotrophic processes. The high range of A T variations, combined to temperature changes, has a strong impact on the variability of the seawater p CO 2 ( p CO 2 S W ). Based on Argo float data, an entire annual cycle for p CO 2 S W in the NWLB has been reconstructed in order to estimate the temporal sequence of the potential “source” and “sink” of atmospheric CO 2 . By combining this dataset with previous observations in the NWLB, this study shows a significant ocean acidification and a decrease in the oceanic surface pH T 25 of −0.0024 ± 0.0004 pH T 25 units.a –1 . The changes in the carbonate system are driven by the increase of atmospheric CO 2 but also by unexplained temporal changes in the surface A T content. If we consider that the EMed will, in the future, encounter longer, more intense and warmer summer seasons, this study proposes some perspectives on the carbonate system functioning of the “future” EMed.

Genomic signatures of clonality in the deep water kelp Laminaria rodriguezii - Lauric Reynes; Thierry Thibaut; Stéphane Mauger; Aurélie Blanfuné; Florian Holon; Corinne Cruaud; Arnaud Couloux; Myriam Valero; Didier Aurelle (Molecular Ecology, 2021)
The development of population genomic approaches in non‐model species allows for renewed studies of the impact of reproductive systems and genetic drift on population diversity. Here, we investigate the genomic signatures of partial clonality in the deep water kelp Laminaria rodriguezii , known to reproduce by both sexual and asexual means. We compared these results with the species Laminaria digitata , a closely related species that differs by different traits, in particular its reproductive mode (no clonal reproduction). We analysed genome‐wide variation with dd‐RAD sequencing using 4,077 SNPs in L . rodriguezii and 7,364 SNPs in L . digitata . As predicted for partially clonal populations, we show that the distribution of F IS within populations of L . rodriguezii is shifted toward negative values, with a high number of loci showing heterozygote excess. This finding is the opposite of what we observed within sexual populations of L . digitata , characterized by a generalized deficit in heterozygotes. Furthermore, we observed distinct distributions of F IS among populations of L . rodriguezii , which is congruent with the predictions of theoretical models for different levels of clonality and genetic drift. These findings highlight that the empirical distribution of F IS is a promising feature for the genomic study of asexuality in natural populations. Our results also show that the populations of L . rodriguezii analysed here are genetically differentiated and probably isolated. Our study provides a conceptual framework to investigate partial clonality on the basis of RAD‐sequencing SNPs. These results could be obtained without any reference genome, and are therefore of interest for various non‐model species.

Preparing the New Phase of Argo: Scientific Achievements of the NAOS Project - Pierre-Yves Le Traon; Fabrizio D’Ortenzio; Marcel Babin; Edouard Leymarie; Claudie Marec; Sylvie Pouliquen; Virginie Thierry; Cecile Cabanes; Hervé Claustre; Damien Desbruyères; Leo Lacour; Jose-Luis Lagunas; et al. (Frontiers in Marine Science, 2020)

Impacts of Marine and Lagoon Aquaculture on Macrophytes in Mediterranean Benthic Ecosystems - Charles-François Boudouresque; Aurélie Blanfuné; Gérard Pergent; Christine Pergent-Martini; Michèle Perret-Boudouresque; Thierry Thibaut (Frontiers in Marine Science, 2020)

Insights into the species diversity of the genus Sargassum (Phaeophyceae) in the Mediterranean Sea, with a focus on a pre-viously unnoticed taxon from Algeria - MOUNIA AOUISSI; LOUIZA NESRINE SELLAM; CHARLES F. BOUDOURESQUE; AURELIE BLANFUNÉ; FARID DERBAL; HOCINE FRIHI; MICHELE PERRET-BOUDOURESQUE; CHAFIKA REBZANI-ZAHAF; MARC VERLAQUE; THIERRY THIBAUT (Mediterranean Marine Science, 2018)
Nine currently accepted species of the genus Sargassum (Phaeophyceae) have been recorded from the Mediterranean Sea: S. acinarium, S. desfontainesii, S. flavifolium, S. furcatum, S. hornschuchii, S. muticum, S. ramentaceum, S. trichocarpum and S. vulgare. Two of them, S. desfontainesii and S. furcatum, are Atlantic species, the Mediterranean range of which is restricted to the Alboran Sea, close to the Strait of Gibraltar. Three species, S. hornschuchii, S. ramentaceum and S. trichocarpum are endemic to the Mediterranean. The presence of S. flavifolium in the Mediterranean, a north-eastern Atlantic species, is at least in part based upon a misidentification and therefore requires confirmation. A taxon collected near Algiers and Annaba (Algeria), here referred to as ‘Sargassum sp. from Algeria’, although sharing most characters with S. flavifolium, also presents some distinctive characters. In the absence of genetic data, confirming or not its taxonomic value, and in the lack of studies on the herbaria containing the types of many species currently considered as synonyms of S. flavifolium, but which are possible candidates for accommodating the Algerian specimens, the authors prefer a conservative approach. They do not describe a new species, which would be premature, but draw attention to a taxon which may be more widely distributed in the Mediterranean rather than solely along the Algerian coasts.

The Sargassum conundrum: very rare, threatened or locally extinct in the NW Mediterranean and still lacking protection - Thierry Thibaut; Aurélie Blanfuné; Marc Verlaque; Charles-François Boudouresque; Sandrine Ruitton (Hydrobiologia, 2016)

The necromass of the Posidonia oceanica seagrass meadow: fate, role, ecosystem services and vulnerability - Charles F. Boudouresque; Gérard Pergent; Christine Pergent-Martini; Sandrine Ruitton; Thierry Thibaut; Marc Verlaque (Hydrobiologia, 2016)

Exposure to vancomycin causes a shift in the microbial community structure without affecting nitrate reduction rates in river sediments - Anniet M. Laverman; Thibaut Cazier; Chen Yan; Céline Roose-Amsaleg; Fabienne Petit; Josette Garnier; Thierry Berthe (Environmental Science and Pollution Research, 2015)

Distribution and abundance of Ostreopsis spp. and associated species (Dinophyceae) in the northwestern Mediterranean: the region and the macroalgal substrate matter - Aurélie Blanfuné; Charles François Boudouresque; Hubert Grossel; Thierry Thibaut (Environmental Science and Pollution Research, 2015)

Direct evidence for gray seal ( Halichoerus grypus ) predation and scavenging on harbor porpoises ( Phocoena phocoena ) - Thibaut Bouveroux; Jeremy J. Kiszka; Michael R. Heithaus; Thierry Jauniaux; Sylvain Pezeril (Marine Mammal Science, 2014)

Histopathological lesions and DNA adducts in the liver of European flounder (Platichthys flesus) collected in the Seine estuary versus two reference estuarine systems on the French Atlantic coast - Jérôme Cachot; Yan Cherel; Thibaut Larcher; Annie Pfohl-Leszkowicz; Jean Laroche; Louis Quiniou; Jocelyne Morin; Julien Schmitz; Thierry Burgeot; Didier Pottier (Environmental Science and Pollution Research, 2013)

First characterization of eight polymorphic microsatellites for Cystoseira amentacea var. stricta (Fucales, Sargassaceae) - Pauline Robvieux; Julie Videment; Cecile Ribout; Didier Forcioli; Alexandre Meinesz; Thierry Thibaut; Lorraine Bottin (Conservation Genetics Resources, 2012)

The Benefits of Cooperation Under Uncertainty: the Case of Climate Change - Thierry Bréchet; Julien Thénié; Thibaut Zeimes; Stéphane Zuber (Environmental Modeling & Assessment, 2012)

Invasive alga Caulerpa racemosa var. cylindracea makes a strong impact on the Mediterranean sponge Sarcotragus spinosulus - Ante Žuljević; Thierry Thibaut; Marija Despalatović; Jean-Michel Cottalorda; Vedran Nikolić; Ivan Cvitković; Boris Antolić (Biological Invasions, 2011)

Comparison of the Wound-Activated Transformation of Caulerpenyne by Invasive and Noninvasive Caulerpa Species of the Mediterranean - Verena Jung; Thierry Thibaut; Alexandre Meinesz; Georg Pohnert (Journal of Chemical Ecology, 2002)

The Introduced Green Alga Caulerpa Taxifolia Continues to Spread in the Mediterranean - Alexandre Meinesz; Thomas Belsher; Thierry Thibaut; Boris Antolic; Karim Ben Mustapha; Charles-Francçois Boudouresque; Danièle Chiaverini; Francesco Cinelli; Jean-Michel Cottalorda; Aslam Djellouli; Amor El Abed; Carla Orestano; et al. (Biological Invasions, 2001)